Ternary composite material, preparation method thereof and microwave absorbing material

By using a ternary composite material of sheet magnetic metal, amorphous titanium dioxide and non-metallic two-dimensional materials, the problem of difficult dielectric matching of existing microwave absorbing materials when the thickness is less than 1.5mm is solved, and efficient electromagnetic wave absorption performance is achieved.

CN119364738AActive Publication Date: 2025-01-24TSINGHUA UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411294588.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-24
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

When the thickness of existing microwave absorbing materials is less than 1.5mm, it is difficult to achieve wide-band dielectric matching under the real-part conditions of higher dielectric coefficients, resulting in poor electromagnetic wave absorption performance.

Method used

Using ternary composite materials, including sheet magnetic metal, amorphous titanium dioxide and non-metallic two-dimensional materials, through appropriate mass ratios and preparation methods, the synergy of the dielectric properties and magnetic properties of the materials is improved.

Benefits of technology

The synergy of dielectric matching and significant magnetic loss under higher real part of dielectric coefficient is achieved, ensuring that the effective absorption bandwidth of microwave absorbing materials in the 2GHz-18GHz band is greater than 5GHz, and is still highly efficient even when the thickness is less than 1.5mm electromagnetic wave absorption capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119364738A_ABST
    Figure CN119364738A_ABST
Patent Text Reader

Abstract

The invention discloses a ternary composite material, a preparation method thereof and a microwave absorbing material. The ternary composite material comprises flaky magnetic metal, amorphous titanium dioxide and a nonmetal two-dimensional material, wherein the amorphous titanium dioxide and the nonmetal two-dimensional material are attached to the surface of the flaky magnetic metal; the mass ratio of the nonmetal two-dimensional material to the flaky magnetic metal is (0.16-0.4): 1, and the mass ratio of the amorphous titanium dioxide to the flaky magnetic metal is (0.14-0.48): 1. The microwave absorption material comprises a ternary composite material, and when the thickness of the microwave absorption material is smaller than 1.5 mm, the effective absorption bandwidth of the microwave absorption material in the wave band of 2-18 GHz is larger than 5 GHz. Therefore, when the thickness of the microwave absorbing material is smaller than 1.5 mm, the microwave absorbing material still has efficient electromagnetic wave absorbing capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of microwave absorbing materials, and in particular, to a ternary composite material and a preparation method thereof, and a microwave absorbing material. Background Art

[0002] With the development of communication technology, in the field of civilian electronic devices, the electromagnetic radiation generated by electronic equipment poses a potential threat to the operation of precision electronic instruments and human health. Therefore, the management and protection of electromagnetic radiation has become an increasingly important issue; in the field of military weapons and equipment, with the development of radar detection technology, the penetration capability of aircraft and missiles has gradually become the key to victory on the battlefield. Microwave absorbing materials, as a functional material that can convert electromagnetic wave energy into thermal energy, can effectively reduce the reflection of electromagnetic waves. Microwave absorbing materials can not only reduce the degree of damage to precision electronic instruments and human health caused by electromagnetic waves, but also improve the stealth performance of weapons and equipment in the radar frequency range of 2GHz-18GHz, thereby improving the survival rate of weapons on the battlefield. Therefore, the research and development of new microwave absorbing materials has practical significance and strategic value both in the civilian and military fields.

[0003] It should be noted that the above statements are only used to provide background technical information related to the present application and do not necessarily constitute prior art. Summary of the invention

[0004] In the first aspect of the present application, the present application provides a ternary composite material, including a flaky magnetic metal, and amorphous titanium dioxide and a non-metallic two-dimensional material attached to the surface of the flaky magnetic metal; the mass ratio of the non-metallic two-dimensional material to the flaky magnetic metal is (0.16-0.4):1, and the mass ratio of the amorphous titanium dioxide to the flaky magnetic metal is (0.14-0.48):1. Thus, the ternary composite material with a suitable ratio of flaky magnetic metal, non-metallic two-dimensional material and amorphous titanium dioxide can improve the synergistic effect of the dielectric properties and magnetic properties of the ternary composite material.

[0005] In some embodiments, the flaky magnetic metal includes at least one of iron and its alloys, cobalt and its alloys, and nickel and its alloys. Thus, selecting a suitable type of flaky magnetic metal helps to further improve the magnetic properties of the ternary composite material.

[0006] Preferably, the flaky magnetic metal comprises iron.

[0007] In some embodiments, the non-metallic two-dimensional material includes at least one of graphene, two-dimensional transition metal carbide, two-dimensional transition metal nitride, and two-dimensional transition metal carbonitride. Thus, selecting the appropriate type of non-metallic two-dimensional material helps to further improve the dipole orientation polarization loss of the ternary composite material, thereby further improving the dielectric constant of the ternary composite material.

[0008] Preferably, the non-metallic two-dimensional material includes graphene.

[0009] In some embodiments, the particle size of the flaky magnetic metal is 1 μm-10 μm, the particle size of the amorphous titanium dioxide is 0.1 μm-10 μm, and the particle size of the non-metallic two-dimensional material is 0.1 μm-1 μm. Thus, the ternary composite material composed of different particle sizes helps to enrich the microstructure and interface of the ternary composite material, increase the specific surface area of ​​the ternary composite material, thereby increasing the contact area between the electromagnetic wave and the ternary composite material, and improving the absorption rate of the electromagnetic wave.

[0010] In the second aspect of the present application, the present application provides a method for preparing the aforementioned ternary composite material, comprising: mixing a non-metallic material and an organic amine, and then grinding the mixture to obtain a non-metallic material intercalated with an organic amine; ultrasonically dispersing the non-metallic material intercalated with an organic amine to obtain a non-metallic two-dimensional material intercalated with an organic amine; mixing the non-metallic two-dimensional material intercalated with an organic amine, a flaky magnetic metal, and a titanium dioxide precursor, and stirring the mixture to obtain a ternary composite precipitate, wherein the mass ratio of the non-metallic two-dimensional material intercalated with an organic amine to the flaky magnetic metal is (0.2-1):1, and the mass ratio of the titanium dioxide precursor to the flaky magnetic metal is (0.6-1.6):1; and calcining the ternary composite precipitate to obtain a ternary composite material.

[0011] Thus, through grinding treatment, the non-metallic material and the organic amine are fully mixed, and the friction and shear force generated by the grinding treatment cause the molecular chain of the organic amine to be inserted into the interlayer of the non-metallic material, and the intercalation structure formed expands the interlayer distance of the non-metallic material, thereby increasing the specific surface area and the number of active sites of the non-metallic material. At the same time, the thermal effect generated by the mechanical force during the grinding treatment can further increase the surface energy and reaction activity of the non-metallic material intercalated with the organic amine, providing a basis for the subsequent ultrasonic dispersion treatment of the non-metallic material intercalated with the organic amine. The ultrasonic dispersion treatment can further promote the intercalation effect of the organic amine between the layers of the non-metallic material, and then the cavitation effect and mechanical vibration of the ultrasonic wave are used to fully disperse the non-metallic material intercalated with the organic amine, so that the non-metallic material forms a non-metallic two-dimensional material with a nanosheet structure. Through the stirring treatment, the titanium dioxide precursor is first hydrolyzed to form Ti(OH)4 during the stirring process, and then the non-metallic two-dimensional material intercalated with the organic amine, the flaky magnetic metal and Ti(OH)4 gradually agglomerate, providing a basis for the subsequent calcination treatment of the ternary composite precipitate. By controlling the ratio of the non-metallic two-dimensional material, the flaky magnetic metal and the titanium dioxide precursor intercalated with the organic amine, the content of the non-metallic two-dimensional material, the flaky magnetic metal and the titanium dioxide in the ternary composite material can be controlled. The organic impurities and the excess solvent in the ternary composite precipitate can be removed by calcination, which promotes the phase fusion and structural reorganization inside the ternary composite precipitate, and forms a ternary composite material with flaky magnetic metal, amorphous titanium dioxide and non-metallic two-dimensional material.

[0012] In some embodiments, before mixing the non-metallic two-dimensional material, the flaky magnetic metal and the titanium dioxide precursor with the organic amine intercalation, the flaky magnetic metal is further subjected to organic modification treatment, wherein the organic substance comprises a silane coupling agent, and the silane coupling agent comprises at least one of a methoxysilane coupling agent, an epoxysilane coupling agent, an aminosilane coupling agent and a methacryloxysilane coupling agent. Thus, the functional groups in the organic molecules undergo chemical adsorption with the surface of the flaky magnetic metal, so that more functional groups are attached to the surface of the flaky magnetic metal, thereby increasing the active sites on the surface of the flaky magnetic metal, and providing a basis for the subsequent attachment of the non-metallic two-dimensional material and amorphous titanium dioxide.

[0013] In some embodiments, the grinding process satisfies at least one of the following conditions: the non-metallic material includes at least one of graphite oxide, transition metal carbide, transition metal nitride, and transition metal carbonitride; the organic amine includes at least one of propylamine, n-butylamine, and n-pentylamine; in the grinding process, the mass of the non-metallic material is a, in g, the volume of the organic amine is b, in mL, and a:b is 1:(10-20); the grinding speed of the grinding process is 60rpm-100rpm, and the grinding time of the grinding process is 15min-30min. Thus, selecting a suitable type of non-metallic material facilitates the insertion of organic amine into the interlayer of the non-metallic material to form a non-metallic material with an intercalated structure. Organic amines have long carbon chains and amino groups. Selecting a suitable type of organic amine helps the organic amine to be inserted into the interlayer of the non-metallic material to increase the interlayer spacing of the non-metallic material. Selecting a suitable ratio of non-metallic materials and organic amines helps to further improve the intercalation efficiency of organic amines. Selecting a suitable grinding speed and grinding time helps to control the particle size of the non-metallic material.

[0014] In some embodiments, the ultrasonic dispersion treatment includes: adding the non-metallic material of the organic amine intercalation layer to a first solvent for ultrasonic dispersion treatment, wherein the first solvent includes at least one of methanol, ethanol, and propanol; in the ultrasonic dispersion treatment, the mass of the non-metallic material of the organic amine intercalation layer is c, in g, the volume of the first solvent is d, in mL, and c:d is 1:(300-1000). Thus, selecting a suitable first solvent type helps to improve the dispersibility and stability of the non-metallic material of the organic amine intercalation layer in the first solvent. Selecting a suitable ratio of the non-metallic material of the organic amine intercalation layer to the first solvent helps the non-metallic material of the organic amine intercalation layer to form a uniform suspension in the first solvent.

[0015] In some embodiments, the ultrasonic power of the ultrasonic dispersion treatment is 80W-100W, and the ultrasonic time of the ultrasonic dispersion treatment is 15min-30min. Thus, selecting appropriate ultrasonic power and ultrasonic time helps the non-metallic material to form a non-metallic two-dimensional material with a nanosheet structure.

[0016] In some embodiments, the calcination process satisfies at least one of the following conditions: the protective gas for the calcination process includes at least one of nitrogen and argon; the temperature for the calcination process is 300°C-400°C, and the time for the calcination process is 2h-4h. Thus, selecting appropriate protective gas, calcination temperature and calcination time is helpful to form a ternary composite material with a uniform and stable internal structure.

[0017] In the third aspect of the present application, the present application provides a microwave absorbing material, including the aforementioned ternary composite material, or a ternary composite material obtained by the preparation method of the aforementioned ternary composite material. The microwave absorbing material of the present application has a synergistic effect of dielectric matching and significant magnetic loss under a higher real part of the dielectric constant. When the thickness of the microwave absorbing material of the present application is less than 1.5 mm, the effective absorption bandwidth of the microwave absorbing material in the 2 GHz-18 GHz band is greater than 5 GHz. Therefore, when the thickness of the microwave absorbing material of the present application is less than 1.5 mm, it still has a high efficiency in electromagnetic wave absorption capability. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0019] Figure 1 It is a schematic diagram of the process flow of a method for preparing a ternary composite material in one embodiment of the present application.

[0020] Figure 2 is the X-ray diffraction pattern of the products obtained in Examples 1-3 and Comparative Examples 2-5 of the present application; wherein, Figure 2 Figure (a) is the X-ray diffraction diagram of the products obtained in Examples 1-3 and Comparative Examples 4-5. Figure 2 Figure (b) is the X-ray diffraction pattern of the product obtained in Comparative Example 2-3.

[0021] Figure 3 It is the Raman spectra of Examples 1-3 and Comparative Example 5 in the present application.

[0022] Figure 4 It is the XPS N 1s fine spectrum of Examples 1-3, Comparative Example 1 and Comparative Example 5 in the present application.

[0023] Figure 5 It is a scanning electron microscope image of Example 3 in this application.

[0024] Figure 6 It is the scanning electron microscope energy spectrum diagram of Example 3 in this application.

[0025] Figure 7 This is a distribution diagram of the iron element in the product obtained in Example 3 of the present application.

[0026] Figure 8 This is the distribution diagram of the titanium element in the product obtained in Example 3 of the present application.

[0027] Fig. 9 Spectra of relative complex permittivity and complex magnetic permeability of Examples 1-3 and Comparative Example 5, wherein: Fig. 9 Figure (a) is the real part of the dielectric constant; Fig. 9Figure (b) is the imaginary part of the dielectric constant; Fig. 9 Figure (c) is the dielectric loss tangent diagram; Fig. 9 Figure (d) is the real part of magnetic permeability; Fig. 9 Figure (e) is the imaginary part of magnetic permeability; Fig. 9 Figure (f) is the magnetic loss tangent diagram.

[0028] Fig.10 is the relative complex dielectric constant spectrum of comparative examples 1-3, where: Fig.10 Figure (a) is a real part diagram of the dielectric constant of Comparative Example 1; Fig.10 Figure (b) is the imaginary part of the dielectric constant of Comparative Example 1; Fig.10 Figure (c) is a dielectric loss tangent diagram of Comparative Example 1; Fig.10 Figure (d) is a real part diagram of the dielectric constant of Comparative Example 2-3; Fig.10 Figure (e) is the imaginary part of the dielectric constant of Comparative Example 2-3; Fig.10 Figure (f) is the dielectric loss tangent diagram of Comparative Example 2-3.

[0029] Fig.11 is a reflection loss curve of the materials of Examples 1-3 and Comparative Example 5 at different thicknesses, wherein: Fig.11 Figure (a) is a reflection loss curve diagram of Example 1; Fig.11 Figure (b) is a reflection loss curve diagram of Example 2; Fig.11 Figure (c) is a reflection loss curve diagram of Example 3; Fig.11 Figure (d) is the reflection loss curve of comparative example 5.

[0030] Fig.12 The reflection loss curves of the materials of Examples 1-3 at different thicknesses are shown in FIG. Fig.12 Figure (a) is a reflection loss curve diagram of Comparative Example 1; Fig.12 Figure (b) is a reflection loss curve diagram of Comparative Example 2; Fig.12 Figure (c) is the reflection loss curve of comparative example 3. DETAILED DESCRIPTION

[0031] Hereinafter, the ternary composite material and its preparation method, and microwave absorbing material implementation methods of the present application are specifically disclosed with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0032] " Scope " disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be to include end values ​​or not include end values, and can be combined arbitrarily, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 listed, and if the maximum range values ​​3,4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0033] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0034] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0035] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0036] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.

[0037] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.

[0038] Microwave absorbing materials need to have a certain thickness so that electromagnetic waves can be effectively attenuated inside the microwave absorbing materials and converted into heat energy. When the thickness of the microwave absorbing material is less than 1.5 mm, its microwave absorbing performance is greatly reduced, which limits the application of microwave absorbing materials in the field of material lightweighting.

[0039] In order to reduce the thickness of microwave absorbing materials, according to the Maxwell equations, the thinning strategy of microwave absorbing materials is to increase their dielectric constant or magnetic permeability. Among them, the dielectric constant is easier to achieve a significant increase than the magnetic permeability and is regarded as the key to achieving thinning of microwave absorbing materials. However, with the increase of dielectric constant, if microwave absorbing materials want to show good microwave absorption effect under ultra-thin thickness conditions, they need to satisfy the counterintuitive relationship between the real part of the dielectric constant and the inverse proportional relationship of the dielectric loss tangent within a wider frequency band, that is, have good dielectric matching. Good dielectric matching helps electromagnetic waves to effectively enter the interior of the material. However, for microwave absorbing materials with a thickness of less than 1.5 mm, it is difficult to achieve broadband dielectric matching under the condition of a higher real part of the dielectric constant.

[0040] Therefore, developing a microwave absorbing material that can simultaneously meet the requirements of lightweight materials and have high-efficiency electromagnetic wave absorption performance is an urgent problem that needs to be solved.

[0041] In the first aspect of the present application, a ternary composite material is provided, comprising a flaky magnetic metal, and amorphous titanium dioxide and a non-metallic two-dimensional material attached to the surface of the flaky magnetic metal; the mass ratio of the non-metallic two-dimensional material to the flaky magnetic metal is (0.16-0.4):1, and the mass ratio of amorphous titanium dioxide to the flaky magnetic metal is (0.14-0.48):1.

[0042] The ternary composite material of the present application is based on a flaky magnetic metal as a matrix. The flaky magnetic metal has a high magnetic permeability and magnetic loss characteristics, which plays a role in enhancing the magnetic response in the ternary composite material. At the same time, the flaky morphology of the flaky magnetic metal not only increases the specific surface area of ​​the material, enhances the magnetic interaction, and produces a strong magnetic natural resonance, but also can further improve the magnetic permeability and magnetic loss of the ternary composite material through its anisotropic characteristics. The non-metallic two-dimensional material attached to the surface of the flaky magnetic metal can provide a dipole orientation polarization loss for the ternary composite material because of its high conductivity and large specific surface area, thereby improving the dielectric constant of the ternary composite material. The amorphous titanium dioxide attached to the surface of the flaky magnetic metal is helpful to adjust the dielectric properties of the ternary composite material because of its high polarization characteristics, and its amorphous morphology can provide more defect states to increase the dielectric loss of the ternary composite material, thereby improving the energy conversion efficiency of the ternary composite material. Therefore, the ternary composite material with a suitable ratio of flaky magnetic metal, non-metallic two-dimensional material and amorphous titanium dioxide can improve the synergistic effect of the dielectric properties and magnetic properties of the ternary composite material.

[0043] As an example, the mass ratio of the non-metallic two-dimensional material to the flaky magnetic metal may be 0.16:1, 0.2:1, 0.24:1, 0.28:1, 0.32:1, 0.36:1 or 0.4:1.

[0044] As an example, the mass ratio of amorphous titanium dioxide to the flaky magnetic metal may be 0.14:1, 0.18:1, 0.22:1, 0.26:1, 0.3:1, 0.34:1, 0.38:1, 0.42:1, or 0.48:1.

[0045] In some embodiments, the flaky magnetic metal includes at least one of iron and its alloys, cobalt and its alloys, and nickel and its alloys. Thus, selecting a suitable type of flaky magnetic metal helps to further improve the magnetic properties of the ternary composite material.

[0046] Preferably, the flaky magnetic metal comprises iron, and the microstructure of the iron is in a layered morphology.

[0047] In some embodiments, the non-metallic two-dimensional material includes at least one of graphene, two-dimensional transition metal carbide, two-dimensional transition metal nitride, and two-dimensional transition metal carbonitride. Thus, selecting the appropriate type of non-metallic two-dimensional material helps to further improve the dipole orientation polarization loss of the ternary composite material, thereby further improving the dielectric constant of the ternary composite material.

[0048] In some embodiments, the two-dimensional transition metal carbide satisfies the chemical e C f, wherein M includes at least one of Sc, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, and W, e is 2-4; and f is 1-3.

[0049] As an example, e can be 2, 3 or 4.

[0050] As an example, f can be 1, 2 or 3.

[0051] In some embodiments, the two-dimensional transition metal carbide satisfies the chemical g N h , wherein M includes at least one of Sc, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, and W, g is 2-4; and h is 1-3.

[0052] As an example, g can be 2, 3 or 4.

[0053] As an example, h can be 1, 2 or 3.

[0054] Preferably, the non-metallic two-dimensional material includes graphene.

[0055] In some embodiments, the particle size of the flaky magnetic metal is 1 μm-10 μm, the particle size of the amorphous titanium dioxide is 0.1 μm-10 μm, and the particle size of the non-metallic two-dimensional material is 0.1 μm-1 μm. Thus, the ternary composite material composed of different particle sizes helps to enrich the microstructure and interface of the ternary composite material, increase the specific surface area of ​​the ternary composite material, thereby increasing the contact area between the electromagnetic wave and the ternary composite material, and improving the absorption rate of the electromagnetic wave. At the same time, the flaky magnetic metal with a larger particle size helps to improve the overall mechanical strength of the ternary composite material, so that the ternary composite material has better mechanical stability and durability.

[0056] As an example, the particle size of the flaky magnetic metal may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0057] As an example, the particle size of the amorphous titanium dioxide may be 0.1 μm, 0.5 μm, 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, or 10 μm.

[0058] As an example, the particle size of the non-metallic two-dimensional material may be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm.

[0059] In a second aspect of the present application, the present application provides a method for preparing the aforementioned ternary composite material, referring to Figure 1 , the method comprising:

[0060] S100, mixing the non-metallic material and the organic amine and then grinding them to obtain the non-metallic material with the organic amine intercalation layer.

[0061] Thus, the non-metallic material and the organic amine are fully mixed by grinding, and the friction and shear force generated by grinding cause the molecular chain of the organic amine to be inserted into the interlayer of the non-metallic material, and the intercalation structure formed expands the interlayer distance of the non-metallic material, thereby increasing the specific surface area and the number of active sites of the non-metallic material. At the same time, the thermal effect generated by the mechanical force during the grinding process can further increase the surface energy and reaction activity of the non-metallic material intercalated with the organic amine, providing a basis for the subsequent ultrasonic dispersion treatment of the non-metallic material intercalated with the organic amine.

[0062] In some embodiments, the grinding process satisfies at least one of the following conditions: the non-metallic material includes at least one of graphite oxide, transition metal carbide, transition metal nitride, and transition metal carbonitride; the organic amine includes at least one of propylamine, n-butylamine, and n-pentylamine; during the grinding process, the mass of the non-metallic material is a, in g, the volume of the organic amine is b, in mL, and a:b is 1:(10-20); the grinding speed of the grinding process is 60rpm-100rpm, and the grinding time of the grinding process is 15min-30min. Thus, selecting a suitable type of non-metallic material facilitates the insertion of the organic amine into the interlayer of the non-metallic material to form a non-metallic material with an intercalated structure. The organic amine has a long carbon chain and an amino group. Selecting a suitable type of organic amine helps the organic amine to be inserted into the interlayer of the non-metallic material to increase the interlayer spacing of the non-metallic material. Selecting a suitable ratio of non-metallic materials and organic amines helps to further improve the intercalation efficiency of the organic amine. Selecting a suitable grinding speed and grinding time helps to control the particle size of the non-metallic material.

[0063] As examples, a:b may be 1:10, 1:12, 1:14, 1:16, 1:18, or 1:20.

[0064] As an example, the grinding speed of the grinding process may be 60 rpm, 70 rpm, 80 rpm, 90 rpm or 100 rpm.

[0065] As an example, the grinding time of the grinding process may be 15 min, 20 min, 25 min or 30 min.

[0066] As an example, the grinding process satisfies the following conditions: the non-metallic material includes at least one of graphite oxide, transition metal carbide, transition metal nitride, and transition metal carbonitride; the organic amine includes at least one of propylamine, n-butylamine, and n-pentylamine; during the grinding process, the mass of the non-metallic material is a, in g, the volume of the organic amine is b, in mL, and a:b is 1:(10-20); the grinding speed of the grinding process is 60rpm-100rpm, and the grinding time of the grinding process is 15min-30min.

[0067] S200, performing ultrasonic dispersion treatment on the organic amine intercalated non-metallic material to obtain the organic amine intercalated non-metallic two-dimensional material.

[0068] Therefore, ultrasonic dispersion treatment can further promote the intercalation effect of organic amine between non-metallic material layers, and then use the cavitation effect and mechanical vibration of ultrasound to fully disperse the non-metallic material intercalated with organic amine, so that the non-metallic material forms a non-metallic two-dimensional material with a nanosheet structure.

[0069] In some embodiments, the ultrasonic dispersion treatment comprises: adding the non-metallic material intercalated with an organic amine into a first solvent and performing ultrasonic dispersion treatment.

[0070] In some embodiments, the first solvent includes at least one of methanol, ethanol, and propanol. Thus, selecting a suitable first solvent type helps to improve the dispersibility and stability of the non-metallic material intercalated with the organic amine in the first solvent.

[0071] In some embodiments, during the ultrasonic dispersion treatment, the mass of the non-metallic material of the organic amine intercalation layer is c, in g, the volume of the first solvent is d, in mL, and c:d is 1:(300-1000). Thus, selecting a suitable ratio of the non-metallic material of the organic amine intercalation layer to the first solvent helps the non-metallic material of the organic amine intercalation layer to form a uniform suspension in the first solvent.

[0072] As an example, c:d may be 1:300, 1:400, 1:500, 1:600, 1:700, 1:800, 1:900, or 1:1000.

[0073] In some embodiments, the ultrasonic power of the ultrasonic dispersion treatment is 80W-100W, and the ultrasonic time of the ultrasonic dispersion treatment is 15min-30min. Thus, selecting appropriate ultrasonic power and ultrasonic time helps the non-metallic material to form a non-metallic two-dimensional material with a nanosheet structure.

[0074] As an example, the ultrasonic power of the ultrasonic dispersion treatment may be 80W, 85W, 90W, 95W or 100W.

[0075] As an example, the ultrasonic dispersion treatment may be carried out for 15 min, 20 min, 25 min or 30 min.

[0076] S300, mixing the organic amine intercalated non-metallic two-dimensional material, the flaky magnetic metal, and the titanium dioxide precursor, and stirring to obtain a ternary composite precipitate, wherein the mass ratio of the organic amine intercalated non-metallic two-dimensional material to the flaky magnetic metal is (0.2-1):1, and the mass ratio of the titanium dioxide precursor to the flaky magnetic metal is (0.6-1.6):1.

[0077] First, the titanium dioxide precursor is hydrolyzed to form Ti(OH)4 during stirring, and then the non-metallic two-dimensional material, flaky magnetic metal and Ti(OH)4 intercalated with organic amine gradually agglomerate, providing a basis for the subsequent calcination of the ternary composite precipitate. By controlling the ratio of the non-metallic two-dimensional material, flaky magnetic metal and titanium dioxide precursor intercalated with organic amine, the content of non-metallic two-dimensional material, flaky magnetic metal and titanium dioxide in the ternary composite material can be controlled.

[0078] As an example, the mass ratio of the organic amine intercalated non-metallic two-dimensional material to the flaky magnetic metal can be 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1 or 1:1.

[0079] As an example, the mass ratio of the titanium dioxide precursor to the flaky magnetic metal may be 0.6:1, 0.8:1, 1:1, 1.2:1, 1.4:1 or 1.6:1.

[0080] In some embodiments, before the non-metallic two-dimensional material intercalated with an organic amine, the flaky magnetic metal, and the titanium dioxide precursor are mixed, the flaky magnetic metal is further subjected to an organic modification treatment. Thus, the functional groups in the organic molecules chemically adsorb to the surface of the flaky magnetic metal, so that more functional groups are attached to the surface of the flaky magnetic metal, thereby increasing the active sites on the surface of the flaky magnetic metal, and providing a basis for the subsequent attachment of the non-metallic two-dimensional material and the amorphous titanium dioxide.

[0081] In some embodiments, the organic matter includes a silane coupling agent, and the silane coupling agent includes at least one of a methoxysilane coupling agent (KH540), an epoxysilane coupling agent (KH560), an aminosilane coupling agent (KH550), and a methacryloxysilane coupling agent (KH570). Thus, by selecting a suitable type of silane coupling agent, different types of functional groups can be attached to the surface of the flaky magnetic metal, thereby further increasing the active sites on the surface of the flaky magnetic metal.

[0082] In some embodiments, the step of performing organic modification treatment on the flaky magnetic metal includes: mixing the flaky magnetic metal, the organic matter, and the second solvent, and then performing a first ultrasonic treatment to obtain a first suspension; mixing the first suspension and ammonia water, and then performing a second ultrasonic treatment to obtain a second suspension; and filtering the second suspension to obtain the flaky magnetic metal modified with organic matter. Thus, during the first ultrasonic treatment, the flaky magnetic metal and the organic matter are uniformly suspended in the second solvent, and during the second ultrasonic treatment, the ammonia water helps the functional groups in the organic molecules to chemically adsorb on the surface of the flaky magnetic metal, thereby grafting the organic matter onto the flaky magnetic metal; and finally filtering the second suspension to obtain the flaky magnetic metal modified with organic matter.

[0083] In some embodiments, the mass of the flaky magnetic metal is i, in g, the volume of the organic matter is j, in mL, and the ratio of i:g is 2:(0.5-1.5).

[0084] As examples, i:g may be 2:0.5, 2:1, or 2:1.5.

[0085] In some embodiments, the mass of the flaky magnetic metal is i, in g, the volume of the second solvent is k, in mL, and i:k is 1:(10-30).

[0086] As examples, i:k may be 1:10, 1:15, 1:20, 1:25, or 1:30.

[0087] In some embodiments, the mass of the flaky magnetic metal is i, in g, the volume of the ammonia water is l, in mL, and i:l is 1:(0.1-0.3).

[0088] As examples, i:1 may be 1:0.1, 1:0.15, 1:0.2, 1:0.25, or 1:0.3.

[0089] In some embodiments, the second solvent includes at least one of ethanol and isopropanol.

[0090] In some embodiments, the ultrasonic power of the first ultrasonic treatment is 80W-100W, and the ultrasonic time of the first ultrasonic treatment is 20min-40min, thereby helping the flaky magnetic metal and organic matter to be further evenly suspended in the second solvent.

[0091] As an example, the ultrasound power of the first ultrasound treatment may be 80W, 85W, 90W, 95W or 100W.

[0092] As an example, the sonication time of the first sonication may be 20 min, 25 min, 30 min, 35 min or 40 min.

[0093] In some embodiments, the ultrasonic power of the second ultrasonic treatment is 80W-100W, and the ultrasonic time of the second ultrasonic treatment is 1h-3h, thereby facilitating the chemical adsorption of the functional groups in the organic molecules onto the surface of the flaky magnetic metal.

[0094] As an example, the ultrasound power of the second ultrasound treatment may be 80W, 85W, 90W, 95W or 100W.

[0095] As an example, the sonication time of the second sonication may be 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0096] In some embodiments, the organic-modified flaky magnetic metal is washed to obtain the washed organic-modified flaky magnetic metal, thereby obtaining an organic-modified flaky magnetic metal with a higher purity.

[0097] In some embodiments, the wash solvent of the wash treatment comprises anhydrous ethanol.

[0098] In some embodiments, the washed organic-modified flaky magnetic metal is dried in a vacuum environment.

[0099] In some embodiments, the drying temperature of the drying process is 30° C.-50° C., and the drying time of the drying process is 1 h-3 h.

[0100] As an example, the drying temperature of the drying process may be 30°C, 35°C, 40°C, 45°C or 50°C.

[0101] As an example, the drying time of the drying process may be 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0102] In some embodiments, the vacuum degree of the vacuum environment is less than 1 kPa.

[0103] As an example, the vacuum degree of the vacuum environment includes, but is not limited to, 0.1 kPa, 0.3 kPa, 0.5 kPa, 0.7 kPa, or 0.9 kPa.

[0104] In some embodiments, the titanium dioxide precursor includes at least one of tetrabutyl titanate, tetraisopropyl titanate, n-butyl titanate, ethyl titanate, and tetramethyl titanate.

[0105] In some embodiments, the stirring speed of the stirring process is 500 rpm-1000 rpm, and the stirring time of the stirring process is 1 h-3 h, so that the titanium dioxide precursor is fully hydrolyzed.

[0106] As an example, the stirring rotation speed of the stirring process may be 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, or 1000 rpm.

[0107] As an example, the stirring time of the stirring process may be 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0108] S400, calcining the ternary composite precipitate to obtain a ternary composite material. Thus, the calcination process can remove organic impurities and excess solvent in the ternary composite precipitate, promote phase fusion and structural reorganization inside the ternary composite precipitate, and form a ternary composite material having flaky magnetic metal, amorphous titanium dioxide and non-metallic two-dimensional material.

[0109] In some embodiments, the calcination process satisfies at least one of the following conditions: the protective gas for the calcination process includes at least one of nitrogen and argon; the temperature for the calcination process is 300°C-400°C, and the calcination process time is 2h-4h. Therefore, selecting appropriate protective gas, calcination process temperature and calcination process time is helpful to form a ternary composite material with a uniform and stable internal structure.

[0110] As an example, the temperature of the calcination process may be 300°C, 320°C, 340°C, 360°C, 380°C, or 400°C.

[0111] As an example, the calcination treatment time may be 2 h, 2.5 h, 3 h, 3.5 h or 4 h.

[0112] As an example, the calcination treatment satisfies the following conditions: the protective gas of the calcination treatment includes at least one of nitrogen and argon; the temperature of the calcination treatment is 300° C.-400° C., and the time of the calcination treatment is 2 h-4 h.

[0113] In the third aspect of the present application, the present application provides a microwave absorbing material, including the aforementioned ternary composite material, or, a ternary composite material obtained by the preparation method of the aforementioned ternary composite material. The microwave absorbing material of the present application has a synergistic effect of dielectric matching and significant magnetic loss under a higher real part of the dielectric constant. When the thickness of the microwave absorbing material of the present application is less than 1.5 mm, the effective absorption bandwidth of the microwave absorbing material in the 2 GHz-18 GHz band is greater than 5 GHz. Therefore, when the thickness of the microwave absorbing material of the present application is less than 1.5 mm, it still has a high efficiency in electromagnetic wave absorption capability.

[0114] In some embodiments, the microwave absorbing material further includes an organic binder, whereby the organic binder can improve the formability of the microwave absorbing material, so that the microwave absorbing material can be processed into a desired shape and size to meet actual use requirements.

[0115] In some embodiments, the organic binder includes at least one of paraffin and resin.

[0116] In some embodiments, based on the total mass of the microwave absorbing material, the mass fraction of the ternary composite material is 50%-70%. Thus, the thickness and electromagnetic wave absorption capacity of the microwave absorbing material can be further optimized.

[0117] As an example, the mass fraction of the ternary composite material may be 50%, 55%, 60%, 65% or 70% based on the total mass of the microwave absorbing material.

[0118] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.

[0119] Example 1

[0120] (1) Preparation of organic-modified flaky iron powder

[0121] S100, 4 g of flaky iron powder, 2 mL of KH540, and 100 mL of isopropanol were mixed and subjected to a first ultrasonic treatment, wherein the ultrasonic power of the first ultrasonic treatment was 80 W, and the ultrasonic time of the first ultrasonic treatment was 30 min, to obtain a first suspension;

[0122] S200, after adding 1 mL of ammonia water and 6 mL of deionized water to the first suspension, perform a second ultrasonic treatment, wherein the ultrasonic power of the second ultrasonic treatment is 80 W, and the ultrasonic time of the second ultrasonic treatment is 1 h, to obtain a second suspension;

[0123] S300, filtering the second suspension to obtain powder, washing the powder three times with anhydrous ethanol, and drying the powder at 45° C. in a vacuum environment for 1 hour, wherein the vacuum degree of the vacuum environment is 0.9 kPa; after drying, grinding the powder into fine powder to obtain organic-modified flaky iron powder.

[0124] (2) Preparation of ternary composite materials

[0125] S100, taking 0.1 g of graphite oxide and pouring it into a mortar, adding 1 mL of n-butylamine dropwise into the mortar, and grinding it, the grinding speed of the grinding treatment is 60 rpm, and the grinding time is 20 min, so as to obtain graphite oxide intercalated with n-butylamine;

[0126] S200, placing the graphite oxide intercalated with n-butylamine in a glass bottle, adding 100 mL of anhydrous ethanol to the glass bottle, and performing ultrasonic dispersion treatment, wherein the ultrasonic power of the ultrasonic dispersion treatment is 80 W and the ultrasonic time is 15 min to obtain a dispersion of graphene oxide nanosheets intercalated with n-butylamine;

[0127] S300, adding 0.5 g of organic-modified flaky iron powder to the dispersion of n-butylamine intercalated graphene oxide nanosheets, and mechanically stirring for 1 h at a stirring speed of 500 rpm; then adding 0.423 g of tetrabutyl titanate dropwise, and continuing to mechanically stir for 2 h at a stirring speed of 500 rpm; after the stirring is completed, naturally drying to obtain a ternary composite precipitate;

[0128] The dispersion of graphene oxide nanosheets intercalated with n-butylamine contains 0.2 g of graphene oxide nanosheets intercalated with n-butylamine;

[0129] S400, grinding the ternary composite precipitate into powder, and calcining it in a nitrogen atmosphere, the calcination temperature of the calcination treatment is 300 ° C, the calcination time is 2h, and after the calcination is completed, the powder is cooled to room temperature to obtain a product ternary composite material, recorded as RTF-1.

[0130] Example 2

[0131] The difference between Example 2 and Example 1 is that the amount of tetrabutyl titanate added is 0.468 g, and the obtained ternary composite material is recorded as RTF-2.

[0132] Example 3

[0133] The difference between Example 3 and Example 1 is that the amount of tetrabutyl titanate added is 0.508 g, and the obtained ternary composite material is recorded as RTF-3.

[0134] Comparative Example 1

[0135] 0.5 g of graphite oxide was poured into a mortar, 5 mL of n-butylamine was added dropwise into the mortar, and then grinding was performed. The grinding speed of the grinding treatment was 60 rpm and the grinding time was 30 min to obtain n-butylamine intercalated graphite oxide; the n-butylamine intercalated graphite oxide was placed in a glass bottle, 200 mL of anhydrous ethanol was added into the glass bottle, and then ultrasonic dispersion was performed. The ultrasonic power of the ultrasonic dispersion was 80 W and the ultrasonic time was 15 min to obtain n-butylamine intercalated graphene oxide nanosheet dispersion; after the n-butylamine intercalated graphene oxide nanosheet dispersion was naturally dried, it was ground into powder and calcined in a nitrogen atmosphere. The calcination temperature of the calcination treatment was 300 ° C and the calcination time was 2 h. After the calcination was completed, the powder was cooled to room temperature to obtain the product graphene, recorded as rGO.

[0136] Comparative Example 2

[0137] 100 mL of anhydrous ethanol was measured, and 1.99 g of tetrabutyl titanate was added dropwise under magnetic stirring. The mechanical stirring was continued at a stirring speed of 500 rpm for 2 h. After the stirring was completed, the mixture was naturally dried to obtain a hydrolysis precipitate. The hydrolysis precipitate was ground into powder, and then calcined in an air atmosphere at a calcination temperature of 300 ° C and a calcination time of 2 h. After the calcination was completed, the powder was cooled to room temperature to obtain the product titanium dioxide, recorded as TiO2-1.

[0138] Comparative Example 3

[0139] The difference between Comparative Example 3 and Comparative Example 2 is that the calcination treatment is carried out under a nitrogen atmosphere, and the obtained titanium dioxide product is recorded as TiO2-2.

[0140] Comparative Example 4

[0141] 4 g of flaky iron powder, 2 mL of KH540, and 100 mL of isopropanol were mixed and subjected to a first ultrasonic treatment, wherein the ultrasonic power of the first ultrasonic treatment was 80 W and the ultrasonic time of the first ultrasonic treatment was 30 min, to obtain a first suspension;

[0142] After adding 1 mL of ammonia water and 6 mL of deionized water to the first suspension, a second ultrasonic treatment is performed, wherein the ultrasonic power of the second ultrasonic treatment is 80 W and the ultrasonic time of the second ultrasonic treatment is 1 h, to obtain a second suspension;

[0143] The second suspension is filtered to obtain a powder, and the powder is washed three times with anhydrous ethanol, and then the powder is placed in a vacuum environment and dried at 45° C. for 1 hour, and the vacuum degree of the vacuum environment is 0.9 kPa; after drying, the powder is ground into fine powder to obtain organic-modified flaky iron powder;

[0144] The organic-modified flaky iron powder was ground into powder and then calcined in a nitrogen atmosphere at a calcination temperature of 300° C. for 2 h. After calcination, the powder was cooled to room temperature to obtain the product flaky iron powder, which was recorded as FCI.

[0145] Comparative Example 5

[0146] The difference between Example 5 and Example 1 is that the amount of tetrabutyl titanate added is 0.847 g, and the obtained ternary composite material is recorded as RTF-4.

[0147] The products obtained in Examples 1-3 and Comparative Examples 1-5 were subjected to performance tests, and the performance test items were as follows:

[0148] (1) X-ray diffraction (XRD)

[0149] The products obtained in Examples 1-3 and Comparative Examples 2-5 were subjected to XRD testing. The XRD patterns are shown in Figure 2 shown.

[0150] Since the raw materials of Examples 1-3 and Comparative Examples 4-5 contain iron, an X-ray diffractometer (Bruker D8 Advance) with a cobalt target was used to test the products of Examples 1-3 and Comparative Examples 4-5. The test results are as follows: Figure 2 As shown in Figure (a), the products obtained in Examples 1-3 and Comparative Examples 4-5 contain flaky iron powder phase components, that is, the ternary composite material of the present application contains flaky iron powder.

[0151] The product of Comparative Example 2-3 was tested using an X-ray diffractometer (Rigaku D / max 2500) with a copper target. The test results are as follows: Figure 2 As shown in Figure (b), the diffraction peak of TiO2-1 of Comparative Example 2 can be well matched with the PDF card (#21-1272) of anatase phase titanium dioxide, which shows that crystalline titanium dioxide can be obtained by calcining in air atmosphere. The diffraction peak of TiO2-2 of Comparative Example 3 is only a mantou peak, which shows that amorphous titanium dioxide can be obtained by calcining in nitrogen atmosphere. Figure 2 The test results of Examples 1-3 and Comparative Example 5 in Figure (a) show that there are no other obvious diffraction peaks except the diffraction peak of flaky iron powder, which can indirectly indicate that the products obtained in Examples 1-3 and Comparative Example 5 contain amorphous titanium dioxide phase components, that is, the ternary composite material of the present application contains amorphous titanium dioxide.

[0152] (2) Raman spectroscopy

[0153] The products obtained in Examples 1-3 and Comparative Example 5 were subjected to Raman spectroscopy testing. The testing instrument model was Horiba Lab RAM HR Evolution, and the excitation light source wavelength was 514 nm. The Raman spectra were as shown in the figure below: Figure 3 shown.

[0154] Depend on Figure 3 It can be seen that the products obtained in Examples 1-3 and Comparative Example 5 have a -1 and -1590cm -1 There are Raman peaks at , which correspond to the D peak and G peak of graphene respectively. It can be explained that the products obtained in Examples 1-3 and Comparative Example 5 contain graphene phase components, that is, the ternary composite material of the present application contains graphene.

[0155] (3) X-ray photoelectron spectroscopy (XPS)

[0156] The products obtained in Examples 1-3, Comparative Example 1, and Comparative Example 5 were subjected to XPS N 1s testing using a Thermo Fisher ESCALAB 250Xi instrument. The XPS N 1s fine spectra are shown in Figure 2. Figure 4 shown.

[0157] Depend on Figure 4 It can be seen that Examples 1-3, Comparative Example 1, and Comparative Example 5 have relatively obvious main peaks at around 400 eV, corresponding to pyrrole N, and the main peak shapes of Examples 1-3, Comparative Example 5 and Comparative Example 1 are very similar, which can explain that the graphene in the products obtained in Examples 1-3 and Comparative Example 5 is doped with nitrogen atoms, and the nitrogen atoms are introduced by n-butylamine after intercalation and then thermal reduction.

[0158] (4) Scanning electron microscopy

[0159] The product obtained in Example 3 was scanned by electron microscope. The testing instrument model was Hitachi SU8600. The scanning electron microscope (SEM) image was as follows: Figure 5 As shown in the scanning electron microscope energy spectrum (EDS) diagram Figure 6 Further, Figure 7 This is a distribution diagram of the iron element in the product obtained in Example 3 of the present application. Figure 8 This is a distribution diagram of the titanium element in the product obtained in Example 3 of the present application. Figure 7 and Figure 8 is based on Figure 6 The overall element distribution diagram is obtained.

[0160] Depend on Figure 5 It can be seen that graphene nanosheets are distributed on the surface of the flaky iron powder, the particle size of the flaky iron powder is 1 μm-10 μm, and the particle size of the graphene is 0.1 μm-1 μm.

[0161] Depend on Figure 6-8 It can be seen that amorphous titanium dioxide is distributed on the surface of the flaky iron powder, and the particle size of the amorphous titanium dioxide is 0.1 μm-10 μm.

[0162] (5) Dielectric constant and magnetic permeability of microwave absorbing materials

[0163] The products obtained in Examples 1-3, Comparative Examples 1-3, and Comparative Example 5 were mixed with paraffin wax respectively, with the mass ratio of the product to the paraffin wax being 3:2, and the mixture was hydraulically pressed to obtain a coaxial ring with an outer diameter of 7 mm, an inner diameter of 3 mm, and a thickness of 1.5 mm. The relative complex permittivity and complex permeability of each coaxial ring were tested using a vector network analyzer (VNA, Agilent PNA-N5244A).

[0164] The relative complex permittivity and complex permeability spectra of Examples 1-3 and Comparative Example 5 are shown in Fig. 9 As shown. Among them, Fig. 9 Figure (a) is the real part of the dielectric constant; Fig. 9 Figure (b) is the imaginary part of the dielectric constant; Fig. 9 Figure (c) is the dielectric loss tangent diagram; Fig. 9 Figure (d) is the real part of magnetic permeability; Fig. 9 Figure (e) is the imaginary part of magnetic permeability; Fig. 9 Figure (f) is the magnetic loss tangent diagram.

[0165] The relative complex permittivity and complex permeability spectra of Comparative Examples 1-3 are shown in Fig.10 As shown. Among them, Fig.10 Figure (a) is a real part diagram of the dielectric constant of Comparative Example 1; Fig.10 Figure (b) is the imaginary part of the dielectric constant of Comparative Example 1; Fig.10 Figure (c) is a dielectric loss tangent diagram of Comparative Example 1; Fig.10 Figure (d) is a real part diagram of the dielectric constant of Comparative Example 2-3; Fig.10 Figure (e) is the imaginary part of the dielectric constant of Comparative Example 2-3; Fig.10 Figure (f) is the dielectric loss tangent diagram of Comparative Example 2-3.

[0166] For the dielectric constant, Fig.10 As shown in Figures (a) to (c), the high conductivity of Comparative Example 1 leads to large dielectric constant and dielectric loss tangent. Although this is conducive to reducing the thickness of the microwave absorbing material, it is also prone to impedance mismatch, resulting in poor microwave absorption performance. Therefore, a low-loss component is required to adjust its dielectric properties. Fig.10 It can be seen from Figures (d) to (f) that due to the presence of a large number of defects in amorphous titanium dioxide, the dielectric constant and dielectric loss tangent of Comparative Example 3 are larger than those of Comparative Example 2. Therefore, amorphous titanium dioxide is more suitable as a component of microwave absorbing materials to adjust the performance of graphene.

[0167] Therefore, if Fig. 9As shown, the microwave absorbing materials of Examples 1-3, whose flaky iron powders are combined with graphene and amorphous titanium dioxide, amorphous titanium dioxide greatly reduces the conductivity of the microwave absorbing material so that the conductivity loss of the microwave absorbing material can be ignored, and greatly reduces the imaginary part of its dielectric constant and dielectric loss tangent; at the same time, the small amount of nitrogen atoms doped in the graphene phase and the small amount of oxygen-containing functional groups remaining after thermal reduction, the defects in the amorphous titanium dioxide phase, and the low-barrier Schottky heterogeneous interface formed by the contact between the graphene phase and the amorphous titanium dioxide phase, slightly increase the polarization loss of the microwave absorbing material, and keep the real part of the dielectric constant relatively large, thus achieving the dielectric matching under the high dielectric constant real part required for the thinned microwave absorbing material. It is worth mentioning that because the content of titanium dioxide in Comparative Example 5 is relatively high, this leads to a significant decrease in both the dielectric constant and the dielectric loss tangent, so that the microwave absorbing material of Comparative Example 5 cannot show sufficient microwave absorption effect at an ultra-thin thickness of less than 1.5 mm.

[0168] For magnetic permeability, Fig. 9 As shown, because the microwave absorbing materials of Examples 1-3 and Comparative Example 5 contain flaky iron powder, the flaky iron powder has a strong magnetic natural resonance and anisotropy of the iron component morphology, so that the real part of the magnetic permeability is greater than 1 in the 2GHz-18GHz frequency band, the imaginary part of the magnetic permeability is greater than 0 in the 2GHz-18GHz frequency band, and the magnetic loss tangent is greater than 0 in the 2GHz-18GHz frequency band, which not only helps to improve the dielectric matching problem of the microwave absorbing material in a wider frequency band, but also helps to further reduce the thickness of the microwave absorbing material.

[0169] (6) Reflection loss of microwave absorbing materials

[0170] The products obtained in Examples 1-3, Comparative Examples 1-3 and Comparative Example 5 were mixed with paraffin respectively, with the mass ratio of each product to paraffin being 3:2, and the mixture was hydraulically formed into a series of coaxial rings of different thicknesses, with the outer diameter of the coaxial rings being 7 mm and the inner diameter being 3 mm.

[0171] Fig.11 It is a reflection loss curve diagram of the materials of Examples 1-3 and Comparative Example 5 at different thicknesses, wherein: Fig.11 Figure (a) is a reflection loss curve diagram of Example 1; Fig.11 Figure (b) is a reflection loss curve diagram of Example 2; Fig.11 Figure (c) is a reflection loss curve diagram of Example 3; Fig.11 Figure (d) in FIG. 5 is a reflection loss curve of comparative example 5. The reflection loss values ​​at different thicknesses are based on Fig. 9 The VNA test results are calculated through the single-layer absorption transmission line model, which can directly reflect the microwave absorption effect of the microwave absorption material.

[0172] Fig.12 It is a reflection loss curve diagram of the materials of comparative examples 1-3 at different thicknesses, wherein: Fig.12 Figure (a) is a reflection loss curve diagram of Comparative Example 1; Fig.12 Figure (b) is a reflection loss curve diagram of Comparative Example 2; Fig.12 Figure (c) in FIG. 1 is a reflection loss curve of comparative example 3. The reflection loss values ​​at different thicknesses are based on Fig.10 The VNA test results are calculated using a single-layer absorption transmission line model, which can directly reflect the microwave absorption effect.

[0173] Depend on Fig.11 and Fig.12 It can be seen that due to the synergistic effect of dielectric matching and significant magnetic loss under the real part of the higher dielectric constant, the microwave absorption performance of Examples 1-3 is significantly optimized compared with Comparative Examples 1-3 and Comparative Example 5, that is, when the thickness of the microwave absorbing material is less than 1.5 mm, an effective absorption bandwidth (EAB) greater than 5 GHz is obtained, and EAB refers to the frequency range in which the reflection loss RL is less than -10 dB at a specific thickness, and / or a minimum reflection loss (RL) less than -40 dB is obtained. min ).

[0174] Specifically, when the thickness of the microwave absorbing material in Example 1 is 1.289 mm, the EAB can reach 5.09 GHz; when the thickness of the microwave absorbing material in Example 2 is 1.46 mm, the EAB can reach 5.33 GHz, which can basically cover the entire Ku band (12 GHz to 18 GHz); in particular, when the thickness of the microwave absorbing material in Example 3 is 1.463 mm, the EAB can reach 5.01 GHz, and the RL min can reach -45.25dB; when the thickness of the microwave absorbing material in Example 3 is 1.496mm, RL min It can be as low as -79.51 dB, which shows that the microwave absorbing material of Example 3 has excellent microwave absorbing performance.

[0175] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A ternary composite material, characterized in that: It includes a flaky magnetic metal, and amorphous titanium dioxide and a non-metallic two-dimensional material attached to the surface of the flaky magnetic metal; the mass ratio of the non-metallic two-dimensional material to the flaky magnetic metal is (0.16-0.4):1, and the mass ratio of the amorphous titanium dioxide to the flaky magnetic metal is (0.14-0.48):

1.

2. The ternary composite material according to claim 1, characterized in that: The flaky magnetic metal includes at least one of iron and its alloys, cobalt and its alloys, nickel and its alloys. Preferably, the flaky magnetic metal includes iron.

3. The ternary composite material according to claim 1, characterized in that: The non-metallic two-dimensional material includes at least one of graphene, two-dimensional transition metal carbide, two-dimensional transition metal nitride, and two-dimensional transition metal carbonitride. Preferably, the non-metallic two-dimensional material includes graphene.

4. The ternary composite material according to claim 1, characterized in that: The particle size of the flaky magnetic metal is 1 μm-10 μm, the particle size of the amorphous titanium dioxide is 0.1 μm-10 μm, and the particle size of the non-metallic two-dimensional material is 0.1 μm-1 μm.

5. A method for preparing the ternary composite material according to any one of claims 1 to 4, characterized in that: include: The non-metallic material and the organic amine are mixed and then ground to obtain the non-metallic material with the organic amine intercalation layer; Performing ultrasonic dispersion treatment on the organic amine intercalated non-metallic material to obtain an organic amine intercalated non-metallic two-dimensional material; The organic amine intercalated non-metallic two-dimensional material, the flaky magnetic metal and the titanium dioxide precursor are mixed and stirred to obtain a ternary composite precipitate, wherein the mass ratio of the organic amine intercalated non-metallic two-dimensional material to the flaky magnetic metal is (0.2-1):1, and the mass ratio of the titanium dioxide precursor to the flaky magnetic metal is (0.6-1.6):1; The ternary composite precipitate is calcined to obtain a ternary composite material.

6. The method according to claim 5, characterized in that Before mixing the non-metallic two-dimensional material intercalated with the organic amine, the flaky magnetic metal and the titanium dioxide precursor, the flaky magnetic metal is further subjected to an organic modification treatment, wherein the organic matter comprises a silane coupling agent, and the silane coupling agent comprises at least one of a methoxysilane coupling agent, an epoxysilane coupling agent, an aminosilane coupling agent and a methacryloxysilane coupling agent.

7. The method according to claim 5 or 6, characterized in that: The grinding process satisfies at least one of the following conditions: The non-metallic material includes at least one of graphite oxide, transition metal carbide, transition metal nitride, and transition metal carbonitride; The organic amine includes at least one of propylamine, n-butylamine and n-pentylamine; In the grinding process, the mass of the non-metallic material is a, in g, the volume of the organic amine is b, in mL, and a:b is 1:(10-20); The grinding speed of the grinding process is 60rpm-100rpm, and the grinding time of the grinding process is 15min-30min.

8. The method according to claim 5 or 6, characterized in that: The ultrasonic dispersion treatment comprises: adding the non-metallic material of the organic amine intercalation layer into a first solvent for ultrasonic dispersion treatment, wherein the first solvent comprises at least one of methanol, ethanol and propanol; In the ultrasonic dispersion treatment, the mass of the non-metallic material of the organic amine intercalation layer is c, in g, the volume of the first solvent is d, in mL, and c:d is 1:(300-1000); Optionally, the ultrasonic power of the ultrasonic dispersion treatment is 80W-100W, and the ultrasonic time of the ultrasonic dispersion treatment is 15min-30min.

9. The method according to claim 5 or 6, characterized in that: The calcination treatment satisfies at least one of the following conditions: The protective gas for the calcination treatment includes at least one of nitrogen and argon; The calcination temperature is 300° C.-400° C., and the calcination time is 2 h-4 h.

10. A microwave absorbing material, characterized in that: The invention comprises the ternary composite material as described in any one of claims 1 to 4, or the ternary composite material prepared by the method as described in any one of claims 5 to 9.

Citation Information

Patent Citations

  • Multilayer-graphene-carried titanium dioxide-ferrotitanium bimetal nanoparticles and preparation method thereof

    CN106512939A

  • Preparation method of reduced graphene oxide / multi-walled carbon nanotube / nickel ferrite three-element nano composite wave-absorbing material

    CN108690556A

  • Rare earth modified graphene copper-based composite material and preparation method and application thereof

    CN114480899A

  • Wave-absorbing material and preparation method thereof

    CN114694942A

  • Graphene-based microwave absorption composite material as well as preparation method and application thereof

    CN117320424A